Mathematic Comic Mobile Learning (MCML) for Class VII - Astuti, Ruly Purbo; Ahmadi, Farid; Utanto, Yuli (Universitas Negeri Semarang, 2022)
This research started from the students' low understanding of the concept of Linear Equation System material and had never the use of comic media during mathematics learning. This study aims to develop and determine the effectiveness of learning using comics media which is carried out with a scientific approach in terms of student learning outcomes, with the subject of One Variable Linear Equation (PLSV) in grade VII A SMP Kanisius St. Yoris Semarang for the academic year 2021/2022. The subjects of this study were students of grade VII A SMP Kanisius St. Yoris Semarang for the academic year 2021/2022. This study uses the type of research ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research instrument used in data collection consisted of (1) respondent (teacher) interview sheets, (2) student learning interest and attention scale sheets using MCML, (3) direct observations on the object of study, (4) documentation, ( 5) learning outcomes test. The data from observations and the scale of student learning interest and attention were analyzed quantitatively using the total score and percentage obtained by each student, then based on the results of the percentage determined the criteria for the effectiveness of student learning as a whole. Data from interviews and documentation were analyzed descriptively qualitatively as a reinforcement of the results of student learning effectiveness. Data on student learning outcomes, namely the results of the initial and final tests were analyzed using the total score of each student and the percentage obtained by all students, then based on the results of the percentage the criteria for the effectiveness of student learning outcomes were determined. The results showed that the application of SPLSV learning with comics media was effective in improving student learning outcomes. According to the criteria for the effectiveness of learning outcomes, qualitatively it shows the effectiveness of high learning outcomes.